Perlindungan Hukum Terhadap Anak Dalam Tindak Pidana Terorisme - Arifin, Samsul (Jurnal Panorama Hukum, 2020)
Terrorism is a criminal act that has such a big threat, the State of the Republic of Indonesia as mentioned in the 1945 Constitution must protect the entire Indonesian people and all of Indonesia's bloodshed. Therefore the State and Government are obliged to protect all of their citizens from the threat of terrorism. Law Number 5 Year 2018 concerned Amendments to Law Number 15 of 2003 that concerned to Determination of Government Regulation in Lieu of Law Number 1 Year 2002 concerned to Eradication of Terrorism Crime was one form of legislative policy in its efforts to eradicate criminal acts of terrorism in Indonesia. Lately, criminal acts of terrorism had not only been carried out by adults, but many children were now involved in terrorism groups. The purpose found out and analyzed the involvement of the state in protecting its citizens who were involved in terrorism groups, and to know what legal protection the state can provide. The method used in this research is normative juridical and statute approach, namely the approach of the Law. The purpose of the results showed protect every child involved with terrorism groups and minimize the occurrence of criminal acts of terrorism. Keywords: Children, Terrorism, Legal Protect